Aligning values and politics : empowerment versus entitlement - Gendre, Michael; Sánchez, Nicolás (University Press of America, 2016)
This book argues that politics must align with the promotion of self-actualization. Combining private property rights with an ethics of responsibility and drawing from the ideas of Immanuel Kant, the book opens the doors to a nonpartisan analysis of income inequality, inheritance, race relations, abortion and governance.